Optical emission of GaN/AlN quantum-wires – the role of charge transfer from a nanowire template. Issue 12 (12th March 2018) - Müßener, Jan; Greif, Ludwig A. Th.; Kalinowski, Stefan; Callsen, Gordon; Hille, Pascal; Schörmann, Jörg; Wagner, Markus R.; Schliwa, Andrei; Martí-Sánchez, Sara; Arbiol, Jordi; Hoffmann, Axel; Eickhoff, Martin
Abstract : One-dimensional GaN quantum-wires grown on nanowire templates exhibit bright and sharp luminescence due to carrier transfer from the nanowire cores. Abstract : We show that one-dimensional (1d) GaN quantum-wires (QWRs) exhibit intense and spectrally sharp emission lines. These QWRs are realized in an entirely self-assembled growth process by molecular beam epitaxy (MBE) on the side facets of GaN/AlN nanowire (NW) heterostructures. Time-integrated and time-resolved photoluminescence (PL) data in combination with numerical calculations allow the identification and assignment of the manifold emission features to three different spatial recombination centers within the NWs. The recombination processes in the QWRs are driven by efficient charge carrier transfer effects between the different optically active regions, providing high intense QWR luminescence despite their small volume. This is deduced by a fast rise time of the QWR PL, which is similar to the fast decay-time of adjacent carrier reservoirs. Such processes, feeding the ultra-narrow QWRs with carriers from the relatively large NWs, can be the key feature towards the realization of future QWR-based devices. While processing of single quantum structures with diameters in the nm range presents a serious obstacle with respect to their integration into electronic or photonic devices, the QWRs presented here can be analyzed and processed using existing techniques developed for single NWs.